The Concept of Differentiated Teaching at School Undergoing Reform - Bernotas, Vytautas (Acta Paedagogica Vilnensia, 2002)
The paper deals with a didactic problem – differentiation in the teaching process at school undergoing educational reform. The aim of the study is to present a detailed analysis of the stale of differentiated teaching at some schools of Vilnius and 5 districts. The concept of differentiated teaching, its purposes and tasks are presented. The main causes of insufficient employment of differentiation in the educational process are revealed, and further ways of solving the problem are proposed. It has been established that differentiated teaching not only enables pupils to gain new knowledge from various sources of information, but also teaches them different ways of mastering knowledge, thus developing a self-reliant and creative personality.